2020
DOI: 10.18632/oncotarget.27460
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of a three-scale grading system based on combining molecular imaging with 68Ga-DOTATATE and 18F-FDG PET/CT in patients with metastatic gastroenteropancreatic neuroendocrine neoplasias

Abstract: We investigated on the added prognostic value of a three-scale combined molecular imaging with 68 Ga-DOTATATE and 18 F-FDG PET/CT, (compared to Ki-67 based histological grading), in gastroenteropancreatic neuroendocrine neoplasia patients. 85 patients with histologically proven metastatic gastroenteropancreatic neuroendocrine neoplasias, who underwent combined PET/CT imaging were retrospectively evaluated. Highest Ki-67 value available at time of 18 F-FDG PET/CT was recorded. Patients were classified according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 32 publications
4
33
0
Order By: Relevance
“…To our knowledge, our findings confirm the prognostic value of the NETPET score in bronchial NENs for the first time, extending the findings from previous GEPNEN studies [20,21]. Whilst a similar analysis in bronchial NENs has recently been published and demonstrated a significant proportion of patients with discordant lesions, a different scoring system was used, and the impact of dual PET scoring on overall survival was not reported.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…To our knowledge, our findings confirm the prognostic value of the NETPET score in bronchial NENs for the first time, extending the findings from previous GEPNEN studies [20,21]. Whilst a similar analysis in bronchial NENs has recently been published and demonstrated a significant proportion of patients with discordant lesions, a different scoring system was used, and the impact of dual PET scoring on overall survival was not reported.…”
Section: Discussionsupporting
confidence: 87%
“…Given the different roles of these two scans, we proposed a system to interpret the complementary findings of the two scans -the NETPET score [19]. This score was investigated in a group of predominantly GEPNEN patients, showed prognostic significance independent of histological grade, and was subsequently validated in two other patient cohorts [20,21]. As the prognostic impact of the NETPET score had not been formally investigated in bronchial NENs, we aimed to measure this impact in a retrospective study.…”
Section: Introductionmentioning
confidence: 99%
“…Chromogranin A is well-established as a correlate of disease volume and is associated with survival in previous NET studies. [16][17][18] It was surprising, however, that WHO grade was not associated with OS from the date of the dual-tracer PET, and this was similar to the analyses performed by Chan et al 14 and Karfis et al 15 To investigate this further, we performed a separate survival analysis calculated from the date of histological diagnosis as opposed to the date of the dual-tracer PET, and this did confirm that WHO grade was associated with OS consistent with previous studies. 1,3 It is possible the long latency between the date of histological diagnosis and the date of dual-tracer PET may explain this discrepancy, given that NETs can demonstrate grade evolution over time.…”
Section: Discussionsupporting
confidence: 83%
“…Patients with NETs demonstrating FDG avid disease are at a 10 fold increased risk of death[ 43 ]. Other studies have shown similar findings[ 44 , 45 ].…”
Section: Dotatate Pet Imagingsupporting
confidence: 84%